The Effects of Service Quality, Service Innovation, and Price Perception Toward Household Customer Satisfaction: An Empirical Study - Tripitakananda, Dhevia; Parwati, Kardina Yudha (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The significant growth of the service industry has prompted PLN UP3 Malang, as the main electricity provider in the Malang region, to provide services that meet the needs and desires of customers, particularly in the household segment. This study aims to examine the effects of service quality, service innovation, and price perception toward household customer satisfaction at PT PLN (Persero) UP3 Malang. Data was collected through a questionnaire distributed to 100 residential customers who met the criteria. The collected data was then analyzed using IBM SPSS Statistics 30.0. The results of the study indicate that service quality, service innovation, and price perception have a positive and significant influence on residential customer satisfaction with the services provided by PT PLN (Persero) UP3 Malang.